PROBLEMATIKA SURAT KEPUTUSAN MENTERI LINGKUNGAN HIDUP DAN KEHUTANAN TENTANG STATUS HUTAN DI ATAS TANAH BERSERTIFIKAT HAK MILIK - Ince Aldy Mierald Istiawan (LPPM IAI Almuslim Aceh, 2024)
The problem of the executorial power in the Judicial Review Decision Number 78PK/TUN/2019 is that the execution process was not carried out in the revocation of the Minister of Environment and Forestry's Decree in the Sekaroh Forest area on land owned by the applicant. The issue discussed is the executorial power of the Supreme Court's decision in forcing the parties to carry out the decision's order. This research is normative legal research with a case approach that examines Supreme Court Judicial Review decisions which have permanent legal force and a statutory approach.. As a result of the discussion and research carried out, it can be concluded that the PTUN decision in the Supreme Court decision case Number 78 PK/TUN/2019 has not yet been implemented by the Ministry of Environment and Forestry as the losing party in the decision, so that the applicant for judicial review feels disadvantaged.